Improving teacher education for better Indigenous outcomes : PREEpared : partnering for remote education experience : final report. - Anderson, Peter; Rennie, Jennifer; White, Simone; Darling, Anna (Australia. Dept of Education and Training (DET), 2019)
The PREEpared – Partnering for Remote Education Experience project (formerly known as Improving Teacher Education for Better Indigenous Outcomes) was an initiative seed-funded by the Department of Education (formerly the Office of Learning and Teaching, OLT) in 2016– 2017 and conducted by a project team from Monash University. Data were collected and resources developed in collaboration with a number of teacher educators across Australia who formed a main interview pool, and several members of a diverse expert reference group, whose experience provided a vital, critical reflection on the project's deliverables. The guiding principle for this project was to respond to the staffing needs of remote Indigenous schools and ensure graduate teachers are well-equipped and expertly prepared to work and teach inclusively within and for diverse geographic communities. The project has responded to this aim by providing a central 'go to' website that houses both curriculum and professional experience resources for all initial teacher education providers to access and use. This report details the overarching, well-planned and long-term approach of the project to improve Indigenous outcomes by focusing on improving teacher education. The findings, outcomes and recommendations of this project will ultimately contribute to the employment needs of remote Indigenous schools through the provision of highly trained, confident and culturally responsive teachers. [Executive summary, ed]